LAMP for human African trypanosomiasis: a comparative study of detection formats. - Sally L Wastling; Kim Picozzi; Abbas S L Kakembo; Susan C Welburn (PLoS Neglected Tropical Diseases, 2010)
Loop-mediated isothermal amplification (LAMP) is at the forefront of the search for innovative diagnostics for human African trypanosomiasis (HAT). Several simple endpoint detection methods have been developed for LAMP and here we compare four of these: (i) visualization of turbidity; (ii) addition of hydroxynaphthol blue before incubation; (iii) addition of calcein with MnCl₂ before incubation and (iv) addition of Quant-iT PicoGreen after incubation. These four methods were applied to four LAMP assays for the detection of human African trypanosomiasis, including two Trypanozoon specific and two Trypanosoma brucei rhodesiense specific reactions using DNA extracted from cryo-preserved procyclic form T. b. rhodesiense. A multi-observer study was performed to assess inter-observer reliability of two of these methods: hydroxynapthol blue and calcein with MnCl₂, using DNA prepared from blood samples stored on Whatman FTA cards. Results showed that hydroxynaphthol blue was the best of the compared methods for easy, inexpensive, accurate and reliable interpretation of LAMP assays for HAT. Hydroxynapthol blue generates a violet to sky blue colour change that was easy to see and was consistently interpreted by independent observers. Visible turbidity detection is not possible for all currently available HAT LAMP reactions; Quant-iT PicoGreen is expensive and addition of calcein with MnCl₂ adversely affects reaction sensitivity and was unpopular with several observers.